IMPLEMENTASI DANA DESA UNTUK KEGIATAN PEMBERDAYAAN MASYARAKAT DESA DI KECAMATAN PUCUK KABUPATEN LAMONGAN TAHUN 2018 (Studi Kasus Di Kecamatan Pucuk) - Suyanto Waspo Tondo Wicaksono (Universitas Islam Lamongan, 2020)
ABSTRACT :Permendesa number 19 of 2017 concerning setting priorities for the use of village funds 2018as a guideline for the determination, priorities and use of village funds 2018 that revokesregulations for the development, development of areas left behind, and transmigrationnumber 22 of 2016 concerning setting priorities for the use of village funds in 2017 (StateGazette of 2016 number 1883 ) as amended by village ministerial regulation, underdevelopedregional development, and transmigration number 4 of 2017 concerning changes to villageministerial regulation, underdeveloped regional development, and transmigration number22 of 2016 regarding setting priorities for the use of village funds in 2017. Determination ofpriority use of village funds This aims as a guideline and reference for the implementationof authority, a reference for the Regency / City Regional Government in preparing technicalguidelines for the use of Village Funds and a reference for the Central Regional Governmentin monitoring and evaluating the implementation of the use of the Village Fund. The resultsof research on the implementation of village funds for village community empowermentactivities in Pucuk subdistrict, Lamongan district in 2018 Lamongan Regency, it can beconcluded that the implementation of village fund use activities is in accordance with thepriorities set based on existing regulations, but for community empowerment activities invillages are still relatively minimum and the percentage there is still very little, regardingthe Village Fund policy for village community empowerment activities still needs to beincreased again.Keywords: Implementation, Empowerment, Village Funds.ABSTRAK :Permendesa nomor 19 tahun 2017 tentang penetapan prioritas penggunaan dana desa 2018 Negara republic Indonesia tahun 2016 nomor 1883) sebagaimana telah diubah denganperaturan menteri desa, pembangunan daerah tertinggal, dan transmigrasi nomor 4 tahun2017 tentang perubahan atas peraturan menteri desa, pembangunan daerah tertinggal, dantransmigrasi nomor 22 tahun 2016 tentang penetapan prioritas penggunaan dana desa tahun2017. Penetapan prioritas penggunaan dana Desa ini bertujuan sebagai pedoman dan acuanbagi penyelenggaraan kewenangan, acuan untuk Pemerintah Daerah Kabupaten/Kota dalammenyusun pedoman teknis penggunaan Dana Desa dan acuan bagi Pemerintah Daerah Pusatdalam pemantauan dan evaluasi pelaksanaan penggunaan Dana Desa. Hasil dari penelitiantentang Implementasi dana desa untuk kegiatan pemberdayaan masyarakat desa dikecamatanPucuk kabupaten Lamongan tahun 2018 Kabupaten Lamongan, dapat disimpulkan bahwa Pelaksanaan kegiatan penggunaan dana desa sudah sesuai dengan prioritas yang ditetapkanberdasarkan regulasi yang ada, tetapi untukkegiatan pemberdayaan masyarakat didesa masihrelatif minimum dan prosentasenya masih sangat sedikit, mengenai kebijakan Dana Desa untukkegiatan pemberdayaan masyarakat desa masih perlu untuk ditingkatkan lagi.Kata kunci: Implementasi, Pemberdayaan, Dana Desa.sebagai pedoman penetapan, prioritas dan penggunaan dana desa 2018 haltersebutmencabutperaturanmenteridesa, pembangunandaerahtertinggal, dan transmigrasinomor 22 tahun 2016 tentang penetapan prioritas penggunaan dana desa tahun 2017 (berita